A Novel Synthesis of 1,2,3-Benzotriazinones from 2-(o-Aminophenyl)oxazolines - Fernando Rocha-Alonzo; Daniel Chávez; Adrián Ochoa-Terán; David Morales-Morales; Enrique F. Velázquez-Contreras; Miguel Parra-Hake (Journal of Chemistry)
1,2,3-Benzotriazinones were synthesized in excellent yields by the reaction of 2-(o-aminophenyl)oxazolines and isoamyl nitrite in methanol. The crystal structure of the acetyl derivative of one of the 1,2,3-benzotriazinones provided additional support for the spectroscopic structural characterization of the title compounds.